Marder, T. A. – Wilson Jones, M.: The Pantheon: From Antiquity to the Present. Cambridge University Press. Cambridge 2015. Pp. xix + 471, 24 coloured plates and 165 figures. ISBN 978-0-521-80932-0 - Dobosi, Linda (Dissertationes Archaeologicae, 2017)
x